Penerapan Operasi Matriks pada Analytical Hierarchy Process dalam Pemilihan Kedai Kopi di Kota Palopo - Nugraha, Yuda Satria; Putri Uleng, Budiarti; Mahfuddin, Musyrifah (Yayasan Literasi Sains Indonesia, 2023)
The coffee shop is a culinary business that is growing rapidly in Palopo City. Each coffee shop has its own characteristics and advantages which are used as an attraction to consumers. The purpose of this research is to determine the priority order of consumers in choosing a coffee shop in Palopo City. This research is a quantitative descriptive study with a sample of 3 respondents using a purposive sampling technique. In the data collection process, this study used a questionnaire to collect information in the form of respondents' preferences for the alternatives and criteria being compared. The research method used is the Analytical Hierarchy Process (AHP) which is an analytical method that uses a series of matrix operations to determine the priority order of alternatives based on several criteria with a series of matrix operations to obtain a decision. The results showed that the priority order of the respondents in choosing a coffee shop was based on the factors of variance and taste, location convenience, price affordability, and quality of service, while the priority order of the selected coffee shops was: (1) Kopikoma (38.63% ), (2) Etika (29.79%), (3) Epilog (10.52%), (4) Janji Jiwa (10.44%), and (5) Figura (9.62%).